Pengaruh Profitabilitas, Aset Pajak Tangguhan, Pajak Kini dan Perencanaan Pajak terhadap Manajemen Laba - Alifa Shafiya Nur Hasanah; Indra Pahala; Unggul Purwohedi (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
Effects of operational cash flows, profitability, liquidity, and solvency on financial difficulties in companies in the transport and logistics sector listed on the Indonesian Stock Exchange (IDX) for the period 2020-2022. The study was conducted to determine the impact of profitability, deferred tax assets, current tax expenses, and tax planning on profit management. The study used property and real estate companies listed on the Indonesian Stock Exchange (BEI) during the period 2020-2022 as population. This study method used a quantitative method with data in the form of financial reports available on the IDX website. Samples selected using purposive sampling techniques and produced 66 observational data. Data is processed using SPSS applications and analyzed using logistic regression analysis. This research uses secondary data taken from the company's financial statements. Based on the analysis of this study, it can be concluded that the current tax expense has a positive and significant influence on earnings management, while profitability, deferred tax assets, and tax planning are not significant to earnings management